Learner nurses' perspectives regarding classroom and clinical learning for the regulation 425 program at the University of Limpopo - Moila, Dimakatso Ophilia (University of Limpopo, 2023)
Background: Graduate professional nurses from universities continuously face intellectual scrutiny from nurses who graduated from college, because of the nature of the training programme within the University of Limpopo. Most of the registered nurses perceive learner nurses and community service nurses from universities as those who do not know anything, yet very little is known about the perceptions of learner nurses regarding their training program. Purpose: To investigate how learner nurses in the R425 program perceive their classroom and practical learning. Study method: A quantitative, descriptive cross-sectional method was employed in this study. Data was collected via an online questionnaire from 129 learner nurses with the response rate of 100%, at the University of Limpopo. Data was collected under ten criterion of program review. The data was analyzed using the descriptive statistics from the SPSS tool with the assistance of a statistician. Results: The results of the study showed that the learner nurses had a positive perception on their studies, both theoretical and practical on the seven criterion of program review. However, the criterion on infrastructure and resources, program coordination and learner assessment demonstrated negative perceptions by learner nurses. There was no association between the learner nurses’ choice of study and the outcome of learner nurses performance. Recommendations: vi The researcher recommends adequate staff of theoretical and clinical learning, a balanced program co-ordination on theoretical and practical learning, a better-structured skills lab and enough resources for the learners, and a yearly program review. Conclusion: The results of this study indicate that, the learner nurses enrolled in the nursing department’s R425 program positively perceive their clinical and classroom learning. The study was limited to the university of Limpopo learner nurses, program R425 and cannot be generalized. The study found a few factors that hinder the learner nurses’ learning perspectives, such as lack of support and limited time to clinical areas.
Thesis (M.A. (Nursing)) -- University of Limpopo, 2023
Keywords: Learner nurse; Perspective; Program and clinical learning; Nurses; Perspective; Nursing students; Nursing -- Study and teaching (Associate degree); Nursing -- Study and teaching